Percent composition of essential oil from fresh and dry leaves of pogostemon cablin/ Nurul Syazwani Adam - Adam, Nurul Syazwani (2010)
The essential oil of Pogostemon cablin is mainly contributes to the perfume, cosmetics industries and pharmacological activities. The chemical composition of essential oil extracted from both fresh and dry leaves was studied using hydrodistillation and solvent-extraction methods. The area percent of chemical composition in essential oil was determined by using Gas Chromatography Mass Spectrometry (GC-MS). Five major compounds were identified including patchouli alcohol, a-bulnesene, a-guaiene, a-patchoulene and P-caryophyllene in all four essential oil obtained. However, there were also other compounds present in small area percent of composition. In this study, it shows that essential oil from fresh leaves contains higher area percent of chemical composition compared to dry leaves due to drying effect of dry leaves. Moreover, the higher area percent of chemical composition obtained through solvent-extraction method as compared to hydrodistillation method. This determined by the result obtained in area percent of chemical composition. 80.63% present in fresh leaves essential oil compared to 75.57% in dry leaves essential oil using hydrodistillation method. 82.77%) essential oil extracted from fresh leaves higher than 81.26%> dry leaves essential oil from solvent-extraction method. Therefore, higher chemical composition may be obtained from fresh leaves sample by using solvent-extraction method.